Increased decidual mRNA expression levels of candidate maternal pre-eclampsia susceptibility genes are associated with clinical severity - Yong, H.; Murthi, P.; Borg, A.; Kalionis, B.; Moses, Eric; Brennecke, S.; Keogh, R. (2014)
Introduction: Pre-eclampsia (PE) has a familial association, with daughters of women who had PE during pregnancy having more than twice the risk of developing PE themselves. Through genome-wide linkage and genetic association studies in PE-affected families and large population samples, we previously identified the following as positional candidate maternal susceptibility genes for PE; ACVR1, INHA, INHBB, ERAP1, ERAP2, LNPEP, COL4A1 and COL4A2. The aims of this study were to determine mRNA expression levels of previously identified candidate maternal pre-eclampsia susceptibility genes from normotensive and severe PE (SPE) pregnancies and correlate mRNA expression levels with the clinical severity of SPE. Methods: Third trimester decidual tissues were collected from both normotensive (n = 21) and SPE pregnancies (n = 24) and mRNA expression levels were determined by real-time PCR. Gene expression was then correlated with several parameters of clinical severity in SPE. Statistical significance was determined by Mann–Whitney U test and Spearman's Correlation. Results: The data demonstrate significantly increased decidual mRNA expression levels of ACVR1, INHBB, ERAP1, ERAP2, LNPEP, COL4A1 and COL4A2 in SPE (p < 0.05). Increased mRNA expression levels of several genes – INHA, INHBB, COL4A1 and COL4A2 were correlated with earlier onset of PE and earlier delivery of the fetus (p < 0.05). Conclusion: These results suggest altered expression of maternal susceptibility genes may play roles in PE development and the course of disease severity.